Implementation Of Islamic Religious Guidance And Counseling To Overcome Learning Difficulties In Early Childhood Education RA An-Nur - Salsa Salsa Nur Haliza; Ida Septiani Sari (Prodi Bimbingan dan Konseling Islam (BPI) Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2021)
The purpose of this study was to determine the efforts of supervising teachers in overcoming learning difficulties in early childhood. The object of this research is the supervising teacher from RA An-nur Jakarta. The number of participants involved is three participants. The data and research were collected by interview technique, then the data were analyzed by qualitative descriptive technique. After the data is collected and analyzed, it can be concluded that the efforts of the supervising teacher in overcoming learning difficulties in early childhood at RA An-nur are quite good. The results showed that learning difficulties in early childhood were influenced by two factors, external factors, and internal factors. External factors include: 1.) environmental and community factors 2.) family factors 3.) supervising teacher factors. Internal factors include: 1.) child's age is too young 2.) interest in learning and lack of motivation to learn 3.) low intellectual capacity of emotional condition. The method used by the supervising teacher at RA An-nur to overcome learning difficulties in early childhood uses the Islamic counseling guidance method, namely through example, for example telling stories of the prophets and apostles, educating with love and compassion. Based on the research above, the authors suggest to the supervising teacher RA An-nur to increase creativity in teaching and learning efforts, have skills in diagnosing early childhood who have learning difficulties, and in carrying out services they should work more closely with parents